Hot corrosion behaviour of La2(Zr0.7Ce0.3)2O7 thermal barrier coating ceramics exposed to molten calcium magnesium aluminosilicate at different temperatures. (November 2015) - Zhou, Xin; Zou, Binglin; He, Limin; Xu, Zhenhua; Xu, Jiaying; Mu, Rende; Cao, Xueqiang
Highlights: CMAS reacts with LZ7C3 to form crystalline apatite and fluorite phases. A continuous crystalline layer forms at interface and acts as a CMAS barrier. The morphologies of the corrosion layer are dependent on temperature and time. The rapidly formed apatite crystals appear to be LaO1.5 -lean. The apatite phase is exhibiting chemical composition evolution upon annealing. Abstract: Hot corrosion studies of La2 (Zr0.7 Ce0.3 )2 O7 (LZ7C3) thermal barrier coating (TBC) ceramics by calcium magnesium aluminosilicate (CMAS) glass were conducted at temperatures ranging from 1200 to 1300 °C. Results indicate that CMAS rapidly dissolves LZ7C3 and precipitates apatite phase based on (La, Ca)4 (La, Ce)6 (SiO4 )6 O2, fluorite ZrO2 and other crystalline phases. Those reaction products tend to form a continuous crystalline layer at the CMAS/LZ7C3 interface, which can effectively prevent CMAS from further penetration. However, the apatite crystals appear to be LaO1.5 -lean and are exhibiting chemical composition evolution upon annealing. Those may compromise the effectiveness of LZ7C3 as a CMAS resistant TBC in long-term application.